Implementasi Strategi Pembelajaran Gallery of Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Arab Kelas XI IPA MAN 4 Sleman - Ulfah Hasanah (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2018)
This study aims to determine the implementation of Arabic learning using the Gallery of Learning strategy and is there an increase in student learning outcomes after the Gallery of Learning learning strategy is applied. This research model uses a quasi-experimental design model (Quasi Experiment) with test techniques (pre-test and post-test), observation, interviews, and documentation. Data analysis to test the hypothesis proposed using the